Involvement of hepatitis B X-interacting protein (HBXIP) in proliferation regulation of cells - Wang Feng-ze; Sha Li; Zhang Wei-ying; Wu Lian-ying; Qiao Ling; Li Nan; Zhang Xiao-dong; Ye Li-hong (Acta Pharmacologica Sinica, 2016)
Aim: To investigat the effect of Hepatitis B X-interacting protein (HBXIP) on cell proliferation. Methods: A rabbit antibody against HBXIP was generated. The RNA interference (RNAi) fragment of the HBXIP gene was constructed in the pSilencer-3.0-H1 vector termed pSilencer-hbxip. Plasmids of the pcDNA3-hbxip encoding HBXIP gene and pSilencer-hbxip were transfected into human breast carcinoma MCF-7 cells, hepatoma H7402 cells, and the normal human hepatic cell line L-O2, respectively. 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay and 5-bromo-2-deoxyuridine incorporation assay were applied to detect cell proliferation. MCF-7 cells and L-O2 cells in the cell cycle were examined by flow cytometry. The proteins involved in cell proliferation and cell cycle were investigated by Western blot. Results: Overexpression of HBXIP resulted in the promotion of proliferation of MCF-7, H7402, and L-O2 cells. Flow cytometry showed that the overexpression of HBXIP promoted the cell proliferation of MCF-7 and L-O2 cells, and led to an increased cell proliferative index in MCF-7 cells (from 46.25% to 58.28%) and L-O2 cells (from 29.62% to 35.54%). Western blot showed that expression levels of c-Myc, Bcl-2, and proliferating cell nuclear antigen were upregulated in MCF-7, H7402, or L-O2 cells, whereas that of p27 was downregulated. However, the RNAi of HBXIP brought opposite results. Conclusion: One of the functions of HBXIP is its involvement in cell proliferation.